Occult Papillary Carcinoma of Thyroid with Postoperative Tuberculous Lymphadenitis - Nahar Begum, SM Khodeza; Hannan, ABMA; Islam, Saiful; Uddin, Dayem; Ekram, ARM Saifuddin (TAJ: Journal of Teachers Association, 2011)
A 40-year-old female presented with tuberculous cervical lymphadenopathy developed within three months of total thyroidectomy operation. Her thyroid lesion was a nodular goiter harboring occult papillary carcinoma. Aspiration cytology and histopathology of lymph node revealed granulomatous lymphadenitis of tuberculous type. The patient was treated with conventional antituberculous four-drug regime for 6 months and was followed up for subsequent two years. Our country is considered as an endemic goiter area and Occult papillary carcinoma is therefore, not an uncommon disease here. Tuberculosis is a communicable disease also seen frequently here. But development of tuberculous lymphadenitis in a postoperative Thyroidectomy patient has not been reported before, as per authors knowledge goes. This case has therefore been reported here with a brief review of the literature. This is also emphasized here, that occult papillary carcinoma is possibly a nonlethal curable disease when treated by conservative surgery. Radical surgical or total thyroidectomy is unnecessary in the treatment of the disease. Postoperative nodal metastasis is also of very rare occurrence with these cases. DOI: http://dx.doi.org/10.3329/taj.v14i2.8396 TAJ 2001; 14(2): 92-95